RELATIONAL DATABASE STRUCTURE AND OPERATIONS ENGINEERING USING CLASS DIAGRAM AND ACTIVITY DIAGRAM - Lukman Hakim; M. Sukrisno Mardiyanto (Universitas Bakti Indonesia, 2022)
Software system plays an important role especiallyfor processing large amounts of data. Currently, the operation ofa data is mostly done on the application layer, so the DBMS onlyserves to store data processing results. Data processing on theDBMS layer will make better performance, as it is closer to thephysical data. Application of constraints as well as data accessrights at the DBMS level will apply consistently to the system as awhole so as to maintain data integrity. In this research, UMLbased approach is proposed to map the structure and operationin a domain model into the structure and operation of relationaldatabase. A software will be built using a driven architecturemodel (MDA) to automate the transformation from UML to SQLscript. Class diagrams that describe the domain structure of themodel will be mapped into the table structure on the relationaldatabase, while the Activity diagram that describes thebehavioral aspects of a domain model will be mapped intoprocedure and function. It is expected that this research cansimplify the process of database schema development, increasedata processing speed and maintain data integrity.